Posterior Reversible Encephalopathy Syndrome with Bilateral Independent Epileptic Foci Precipitated By Guillain-Barrè Syndrome - Rosario Rossi; Maria Valeria Saddi; Alessandro Mela; Anna Ticca (Case Reports in Neurological Medicine)
We report the case of a 56-year-old woman who developed status epilepticus (SE) related to independent occipital foci as clinical manifestation of posterior reversible encephalopathy syndrome (PRES) in the background of Guillain-Barrè syndrome (GBS). SE resulted from a series of focal seizures clinically characterized by left- and rightward deviations of the head and consequent oculoclonic movements. Electroencephalography recorded independent seizure activity in both occipital regions with alternate involvement of the two cerebral hemispheres. The epileptic foci corresponded topographically to parenchymal abnormalities of PRES in the occipital lobes. The manifestation of bilateral, independent occipital seizures with alternate deviations of the head and oculoclonic movements, previously not reported in patients with PRES, highlights the acute epileptogenicity of the cerebral lesions in this syndrome. Despite the variable clinical expression of seizures due to occipital damage in PRES, the development of independent seizure activity in both occipital lobes might represent a distinctive epileptic phenomenon of this encephalopathy.